Coaches’ Perspectives on their Roles in Facilitating the Personal Development of Student-Athletes - Banwell, Jenessa; Kerr, Gretchen (Canadian Journal of Higher Education, 2016)
The purpose of this study was to investigate coaches’ perspectives on the personal development student-athletes experience through interuniversity sport. Additionally, it explored the ways in which coaches understand, enable, and facilitate the personal development of student-athletes. Eight in-depth, semi-structured interviews were conducted with male and female head coaches of Canadian Interuniversity Sport programs. A qualitative analysis of the data revealed that the coaches perceived the enhancement of student-athletes’ personal development to be an important part of their role. Despite this claim, the coaches had difficulty in defining personal development and articulating how they facilitated opportunities for athletes’ personal development through sport. The findings from this study have implications for future interuniversity sport programming.